ASESMEN KINERJA PEGAWAI BADAN NARKOTIKA NASIONAL PROVINSI SULAWESI TENGGARA DALAM MENANGGULANGI PEREDARAN NARKOBA DI MASYARAKAT - Darmin Tuwu (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2019)
This study lays out performance assessments of sixteen personnels from the Community Prevention and Empowerment Division of the National Narcotics Agency of Southeast Sulawesi Province in counterbalancing drug abuse and traffic within society. It is a case study with qualitative approach. The data were obtained through in-depth interviews and observations. This study proves out personnels’ performance to be classified as `good`.  According to the assessment scores which were identified by the number 1 to 5, most of the personnels scored 3 (good enough), 4 (good), and 5 (very good). These scores were taken from five criteria of personnel's performance being assessed that includes the performance quality, personnel’s initiatives, and their communication skills. Those three criteria were so prominent that the overall performance quality of Community Prevention and Empowerment Division personnels can be classified as "good" for the following  accomplishments; completing administrative tasks as well as making effective attempts to anticipate drug traffic in the field work. Drug traffic prevention initiatives were carried out in several ways. First, advocating the danger of drug abuse to the public especially the youths. Secondly, extending the training programs to the wider audiences in order to anticipate, counteract, and stop the widespread expansion of narcotics in the community. Finally, incorporating religious values into every campaign, discussion, advocation, and anti-drug training programs initiated by government institutions, private sectors, schools, campuses, and communities to protect the public, particularly the youths from drug abuse and traffic.